analisis pembinaan moral anak jalanan di kota jambi - Oktaviola, Deby; Anderson, Irzal; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2022)
Abstract: This research is motivated by the problems that exist in society that show the problem of bad morals of street children. Where street children do not behave in accordance with existing norms, and perform deviant behavior. The purpose of this study was to collect data on how the Social Service of Jambi City in implementing the moral development of street children, as well as the obstacles that hindered the implementation and the efficacy of moral counseling of street children in the Social Service of Jambi City. Using a combination of interviews and documentation, the qualitative data collection method of this study was considered reliable. A descriptive qualitative approach will be used in this study. Moral education for street children is still not well implemented, concludes this research conducted by the Jambi City Social Service. This is indicated by the existence of obstacles in the implementation of guidance both from facilities and infrastructure in the form of facilities, human resources, officers, or repetition of ignoring the rules on street children in the form of going down on the streets. The conclusion in this study is that the implementation of moral guidance for street children at the Jambi City Social Service is still less effective, which is indicated by the obstacles or problems found by researchers, namely the lack of human resources or officers, lack of facilities/facilities, ineffective time to provide guidance, and the lack of public awareness and attention of parents to their children.